Great teacher creates effective learning environment: a study through IIUM Nursing students’ eyes - Nurumal, Mohd. Said; Jaafar, Rogayah; Arzuman, Hafizah (UKM, 2008)
Learning environment in the universities plays an important role in producing highly competent graduates especially in nursing profession. Thus, the most important as- pects are the teaching activities and as well as student – teacher interaction in daily environment in the university. To investigate the International Islamic University Malay- sia (IIUM) nursing students experience towards their teachers and to identify the rela- tionship between teaching and students learning perception in their learning environ- ment. This study used quantitative method and utilized two out of five subscales in Dundee Ready Educational Environment Measurement (DREEM). The subscales used were students’ perception of learning (SPoL) , students’ perception of teacher (SPoT) and total items in these both subscales are 12 and 11 items, respectively. The ques- tionnaire results revealed that IIUM nursing students scored 28.54/48.00 in (SPoL) and 28.13/44.00 in (SPoT). Both findings showed the IIUM nursing students’ experience their teachers and the learning environment are moving in towards positive directions. The regression finding was 51% of the total variation in students’ perception of teacher score was explained by students’ perception of learning. Although the overall sub- scales (SPoL) score in the current study falls in the category of a more positive per- ception, 2 out of 12 items were poorly scored by the IIUM nursing students. The re- searcher strongly agrees that listening to the expression of students is an important consideration for an educational institution. The overall mean score for (SPoT) showed that the students perceived their teachers as moving in the right direction. In this pre- sent IIUM study, one item showed a mean score of less then 2.00. As a result, these two subscales most probably should reflect the same outcome such as in their aca- demic performance and experience greatly during their student life on campus. The arising issues from this DREEM study at IIUM embrace the need for the creation of supportive environment as well as designing and implementing interventions to remedy unsatisfactorily elements of the learning environment for more effective and successful teaching and learning to be realised.